Analisis Hubungan Kepatuhan Suplementasi Tablet Besi Dengan Karakteristik Ibu Melahirkan Bayi Berat Badan Lahir Rendah di RSUD Wonosari Yogyakarta - Tetie Herlina; Wiwi Kustio Prillia; Danang Prasetyaning Amukti; Ifa Aris Suminingtyas; Nurul Kusumawardani (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
Low birth weight (LBW) is a leading cause of neonatal mortality, especially in developing countries. Previous studies have not comprehensively assessed the role of maternal adherence to iron tablet consumption, gestational age, maternal age, and anemia status. This study aims to analyze the relationship between adherence to iron tablet consumption and the characteristics of mothers who gave birth LBW at Wonosari Regional Hospital, Yogyakarta. This is a retrospective analytical study with a cross-sectional design on 47 pregnant women who gave birth LBW between October 2024 and March 2025. Data collection involved the use of an adherence questionnaire to assess adherence to iron supplementation, as well as secondary data obtained from patient medical records. Statistical analysis was performed using the chi-square test to determine the relationship between variables. The results showed no statistically significant association between adherence to iron supplementation (p=0.74), maternal age (p=0.34), or anemia status (p=0.36) with LBW. However, there was a strong and statistically significant association between gestational age and LBW (p < 0.001), which showed that preterm birth is a major risk factor for LBW. In conclusion, gestational age was significantly associated with LBW, while adherence to iron supplementation, maternal age, and anemia status were not. Preventing preterm birth should be a primary focus in strategies aimed at reducing the incidence of LBW.